The Liquidity Spread: A Parsimonious Method for Data-Scarce Emerging Markets - Melik-Parsadanyan, Vahagn (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
This paper develops a parsimonious method for estimating bond liquidity spreads in emerging markets where transaction data are scarce. It complements earlier work on credit spread decomposition, contributing to a unified valuation framework for data-scarce bond markets. The model was obtained analytically from a one-year holding-period return indifference condition between a liquid and an illiquid bond. It requires only two observable inputs: the bond’s yield bid-ask spread and its modified duration. An extension introduces an adjustment factor to capture volatile market conditions. The central result is a closed-form approximation: the minimum annual liquidity spread equals the product of the bond’s modified duration and its yield bid-ask spread. An illustrative application shows that liquidity costs can outweigh credit risk in thin markets. The framework offers a transparent and replicable alternative to arbitrary mark-ups, addressing a critical gap by providing a dedicated liquidity spread model tailored to data-scarce environments. Its primary innovation lies in its methodological parsimony, delivering a transparent valuation instrument that remains theoretically consistent even in the absence of transaction-level data.